Analisis Kepuasan Pengguna Electronic Health Record (EHR) dengan Menggunakan Metode Delone and Mclean di Unit Rekam Medis RSUPN dr. Cipto Mangunkusumo - Resti Aprilia Tri Hendaryanti; Atma Deharja (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2020)
The rapid development of technology requires humans to move forward to compensate for this. Ease thatis obtained along with technological advancements in carrying out all activities so that the time spentbecomes efficient and can reach wider society. RSUPN Dr. Cipto Mangunkusumo has followedtechnological developments by using EHR which is used to facilitate the process of service in the medicalrecord unit from the patient coming to the patient coming out. EHR at RSUPN Dr. Cipto Mangunkusumostill has shortcomings that is loading long enough 5 minutes for 1 file search that inhibits storage officersand agreement officers in providing patient medical records, other conditions are some menus related toreports are not appropriate and still cannot be accessed so officers must process data in advance to beused as a report and the unavailability of EHR learning modules specifically for new users. The study aimsto analyze the satisfaction of users of EHR at RSUPN Dr. Cipto Mangunkusumo using DeLone andMcLean methods with 6 indicators namely system quality, information quality, use, user satisfaction,individual impact and organizational impact. This type of research used qualitative research with 20respondents. Based on the analysis of user satisfaction it is known that the EHR facilitates the work ofofficers, the information provided is of high quality, the functions provided help the work of officers. It isexpected that the analysis of user satisfaction with EHR can be used as an effort to improve electronicmedical records by adding report print menus, updating servers and creating EHR learning modules.